Towards establishing a network of medical libraries a study of the facilitating and hindering factors that influence networking - Encanto, Joenabie A. (2011)
A library network, as defined by the National Commission on Libraries and Information Science (NCSLIS), is two or more libraries and/or other organizations engaged in a common pattern of information exchange, through communications, for some functional purpose. It usually consists of a formal arrangement whereby materials, information, and services are made available to all potential users.